2021
DOI: 10.1177/21582440211046942
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Targeting the Wellbeing of Migrant Youths: A Systematic Review of the Literature

Abstract: Migration can affect the physical, mental, emotional, and social wellbeing of individuals and families. This study provides an overview of interventions aimed at improving the wellbeing of young migrants. It identifies knowledge gaps and provides direction for future research. The review process comprises a systematic search of six academic databases, and websites for relevant peer-reviewed and gray literature on the topic. A total of 2,911 records were identified, of which 28 studies met our eligibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…We recognise that the CALD Mindfulness Program is only one of a growing number of psychological interventions that have been shown to improve mental health and wellbeing in migrant, refugee and asylum-seeker populations [ 58 , 59 , 60 ]. Other studies conducted among Arabic-speaking adults in Western countries support the use of culturally tailored interventions based on cognitive behaviour therapy (often including a trauma-focused component), problem solving and mind–body techniques such mindfulness, meditation and deep breathing [ 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recognise that the CALD Mindfulness Program is only one of a growing number of psychological interventions that have been shown to improve mental health and wellbeing in migrant, refugee and asylum-seeker populations [ 58 , 59 , 60 ]. Other studies conducted among Arabic-speaking adults in Western countries support the use of culturally tailored interventions based on cognitive behaviour therapy (often including a trauma-focused component), problem solving and mind–body techniques such mindfulness, meditation and deep breathing [ 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning school outcomes, the reviews considered reported marginally significant changes in academic competence [4], but the effects were lower than those obtained through academic programs [40]. On the contrary, there was a positive impact on reducing school stress and increased attention levels [33] and the ability to work with peers was improved [31]. The findings related to health and psychosocial outcomes were also mixed.…”
Section: Social and Emotional Skills Trainingmentioning
confidence: 96%
“…Overall, all the reviews reported some degree of improvement in students' outcomes, even if the effectiveness may have varied from one study to another. In general, expressive techniques are beneficial to all youth, especially when this strategy is implemented to be used with students who have been exposed to traumatic events [33]. Only two reviews partially disagreed with this: Sullivan and Simonson [30] reported less consistent results, and Bal and Perzigian [4] found a decrease in emotional and behavioral symptoms but no significant effects on self-esteem.…”
Section: Creative and Expressive Techniquesmentioning
confidence: 99%
See 2 more Smart Citations